The Communication Strategy of the Depok City Genre Forum Through the "Ini Genting" Campaign Program in Efforts to Prevent Stunting - Maryami, Maryami; Tsabit, Muhammad (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Stunting is a condition of growth failure in children due to chronic malnutrition and recurrent infections in the first 1,000 days of life. One of the causes of the high prevalence of stunting in Indonesia is due to public unawareness and ignorance regarding stunting. The government through DP3AP2KB Depok City and the Depok City Genre Forum developed a communication strategy for the Genting (Real Implementation of Genre to Prevent Stunting) campaign. The goal of the Genting campaign program is to increase synergy between the government and the community in stunting prevention efforts to achieve the zero-stunting target in Depok City. The author uses a qualitative research method, which is carried out by means of observation and interviews with the parties concerned, and the data collected is then analyzed descriptively by describing the results of the research into the form of a research report. The results of the study found that "The Communication Strategy of the Depok City Genre Forum Through the This Campaign Program is Critical in Stunting Prevention Efforts" has gone through stages that are in accordance with the concept of designing a PR campaign according to Anne Gregory, namely starting from problem analysis, setting goals, publics, messages, strategies and tactics, time scales and resources, as well as evaluation and review. The Depok City Genre Forum under the auspices of the Depok City DP3AP2KB carries out information dissemination that is informative, educative and persuasive to increase public awareness and understanding of stunting prevention.